2016
DOI: 10.4014/jmb.1603.03009
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Effects of Various Cultivars of Kiwi Berry (Actinidia arguta) on Lipopolysaccharide-Stimulated RAW 264.7 Cells

Abstract: The present study evaluated the total phenolic and flavonoid contents as well as total antioxidant capacity (TAC) of three cultivars of Actinidia arguta Planch. kiwi berries; cv. Mansoo (Mansoo), cv. Chiak (Chiak), and cv. Haeyeon (Haeyeon). In addition, the anti-inflammatory effects of the three cultivars of kiwi berries were investigated using a lipopolysaccharide (LPS)-stimulated RAW 264.7 murine macrophage cell line. Mansoo had the highest total phenolic content and TAC among the three cultivars, whereas C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 0 publications
3
25
2
1
Order By: Relevance
“…According to Latocha et al [ 17 ], the AA of kiwiberry hydrophilic extracts based on the ABTS assay ranges from 1.73 to 4.22 mg AAE/g FW on average and is similar to that of kiwifruit (1.83–2.06 mg AAE/g FW). These results are comparable to values obtained by An et al [ 43 ] for the kiwiberry in South Korea (1.10–2.10 mg AAE/g FW). Meanwhile Leontowicz et al [ 41 ], using the same assay and solvent, indicate a much higher AA of the kiwiberry (47.2–122.4 μM TE/g DW) compared to kiwifruit (13.5–16.1 μM TE/g DW).…”
Section: Kiwiberry Nutritionsupporting
confidence: 91%
See 2 more Smart Citations
“…According to Latocha et al [ 17 ], the AA of kiwiberry hydrophilic extracts based on the ABTS assay ranges from 1.73 to 4.22 mg AAE/g FW on average and is similar to that of kiwifruit (1.83–2.06 mg AAE/g FW). These results are comparable to values obtained by An et al [ 43 ] for the kiwiberry in South Korea (1.10–2.10 mg AAE/g FW). Meanwhile Leontowicz et al [ 41 ], using the same assay and solvent, indicate a much higher AA of the kiwiberry (47.2–122.4 μM TE/g DW) compared to kiwifruit (13.5–16.1 μM TE/g DW).…”
Section: Kiwiberry Nutritionsupporting
confidence: 91%
“…By contrast, the kiwiberry TPC assayed much higher. According to An et al [ 43 ], the kiwiberry contains 118.2–191.6 mg GAE/100 g FW phenolics, including 28.8–40.4 mg CE/100 g FW flavonoids. Other research has reported the kiwiberry as having phenolics of up to 426 mg as GAE/100 g FW [ 19 , 44 , 45 ], but other studies have reported that the kiwiberry TPC calculated as a sum of all identified compounds ranges from 443.2 to 1301.1 mg/100 g FW and is significantly cultivar dependant [ 20 ].…”
Section: Kiwiberry Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…kiwi fruit also contains other useful compounds such as carotenoids, polyphenols, flavonoids and minerals (Du et al ., ). Polyphenols are abundant in kiwi fruit and are reported to have multiple biological activities, including antioxidant effects in vitro and in vivo (Iwasawa et al ., ), and anti‐inflammatory properties (An et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…따라서 염증 반응에서 염증유발물질인 interferon-, interleukin1- 등의 cytokine과 nitric oxide synthase, cycloxygense-2 등의 발 현 또는 생성 억제를 통하여 nitric oxide와 prostaglandin E 2 의 생성을 억제시키므로 항염증 효과를 확인할 수 있다. 지금까지 항염증 물질생산에 관한 연구로는 적하수오 [4], 홍삼 [5], 홍 자단 [6] 등과 목질진흑버섯 [7,8], 차가버섯(자작나무시루뻔버섯) [9,10], 말굽버섯 [11] 등의 버섯 [1,3,12] 및 키위 [13], 밀배아유 [14], 진두발 [15] 등 주로 약용식물과 천연물 등의 추출 물에서 항염증 효과에 관하여 연구, 보고되었다. 한편, 효모는 진균류의 일종으로 최근 이들 로부터 다양한 대사산물의 생산과 이들에 대한 응용성들이 연구되어 항고혈압성 안지오텐신 전환효소 저해물질 [16][17][18]과 항치매성 B-secretase 저해물질 [19]과 acetylcholine esterase 저 해 물질 [20], 혈전용해 활성물질 [21], 혈관신생 억제물질 [22], 미백성 Tyrosinase 저해물질 YM, PD, YPD, 비타민 무함유 배지 등에서 잘 생육하였다.…”
unclassified